Event Studies in Economics and Finance - MacKinlay, A. Craig (Journal of Economic Literature, 1997)
The event study is an important research tool in economics and finance. The goal of an event study is to measure the effects of an economic event on the value of firms. Event study methods exploit the fact that, given rationality in the marketplace, the effects of an event will be reflected immediately in security prices. Thus the impact can be measured by examining security prices surrounding the event. In this paper event study methods are described including some of the potential complications. An example is included to illustrate the approach.